To adapt or to disregard? Parties’ reactions to external shocks - Calca, P.; Gross, M. (West European Politics, 2019)
How do parties react to unanticipated events such as external shocks? Do they adapt to the consequences of the external shock or do they disregard them? Using the global financial crisis as an empirical example and testing the expectations for parties’ economic policy shifts in 23 European democracies based on Chapel Hill Expert Survey data, the article demonstrates that government parties react more to an external shock than opposition parties, particularly in countries where the external shock has been more severe. This has implications for a broader literature in comparative politics by fostering the dialogue between the political economy literature on external shocks and the literature on party policy shifts by showing the significant impact exogenous events can have on party positioning.